PENENTUAN EFISIENSI KOLEKTOR PELAT DATAR DENGAN PENUTUP KACA PADA SISTEM PEMANAS AIR SURYA - Zelviana '; Maksi Ginting; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted to determine the efficiency of flat plate collector with its cover made from glass. Solar water heaters were made and comprised of five essential components, namely a protective box, a plate absorbent, an insulator, an iron pipe, and a transparent cover. In this study, the water was flown into the water tank, through a collector, and then the water flowed into a tube collectors. The collectors used in this study were flat plate collectors with one and two layer lid. The data was collected within 14 days, starting from 9.00 am until 3.00 pm WIB with one hour time interval. The average efficiency for a single layer collector was 42.62 % to 62.14 % , and for the two layer collectors was 51.69 % to 85.74 % . These results showed that the loss of heat on a flat plate collector with two layer was smaller than those of a single layer collector.